Blood Transfusion in Islam: An Integrative Analysis of Quranic Interpretation, Medical Ethics, and Social Perspectives - Talebe, Tamrin; Harun, Haerani; Musyahidah, Sitti; Attamimi, Suraya (Media Publikasi Cendekia Indonesia, 2025)
This study examines the Islamic bioethical perspective on blood transfusion, a common medical procedure that raises ethical and religious concerns. The research analyzes Quranic verses, hadiths, Islamic jurisprudence, and scholarly interpretations to understand the Islamic stance on blood, its use in medical treatments, and the permissibility of blood transfusion. While blood is generally considered impure in Islam and its consumption is prohibited, exceptions are made for life-saving medical interventions. The study explores the Quranic and hadith-based concepts of blood, its various mentions and contexts in Islamic texts, and how these relate to modern medical practices. It also discusses the medical benefits and risks of blood transfusion, including its life-saving potential and possible complications, within the framework of medical ethics. The research highlights the Islamic principle of preserving life (hifdzu al nafs) and how it applies to blood transfusion. Social aspects, including blood donation as an act of solidarity and charity, are examined through an Islamic lens. The study concludes that blood transfusion is permissible in Islam when medically necessary, aligning with the religion's emphasis on preserving life and helping others. This research contributes to the growing field of Islamic bioethics in contemporary medical practices.